Hyperbaric oxygen exposure alleviate metabolic side-effects of olanzapine treatment and is associated with Langerhans islet proliferation in rats - Mohammad AlQudah; Mohammad Khalifeh; Rasha Al-Azaizeh; Amr Masaadeh; Amr Masaadeh; Omar M. Al-Rusan; Omar M. Al-Rusan; Husam K. Haddad (Frontiers Media S.A., 2022)
Introduction: Olanzapine (OLZ) is one of the second-generation antipsychotics drugs (APDs) used to treat several psychiatric illnesses. Olanzapine treatment is often associated with many metabolic side effects in a dose dependent manner such as obesity, dyslipidemia and insulin resistance, induction of type II diabetes and acute pancreatitis in some patients.Methods: Hyperbaric Oxygen therapy (HBOT) was investigated as a tool to mitigate olanzapine metabolic side effects in rats. Thirty-six female Sprague Dawley (SD) rats were divided into 4 groups; rats on olanzapine treatment either exposed to hyperbaric oxygen therapy (HBOOLZ) or left without exposure (OLZ) then non-treated rats that either exposed to hyperbaric oxygen therapy or left without exposure (control). Rats received Hyperbaric Oxygen therapy for 35 days at 2.4 atmospheres absolute (ATA) for 2.5 h daily followed by intraperitoneal injection of olanzapine at 10 mg/kg or placebo.Results: Rats on either hyperbaric oxygen therapy or olanzapine had a significant loss in body weight. Olanzapine treatment showed a decrease in serum insulin level, triglyceride, highdensity lipoprotein (HDL) cholesterol, and lipase level but an increase in fasting blood sugar (FBS), insulin resistance index (HOMA-IR) and amylase, while rats' exposure to hyperbaric oxygen therapy reversed these effects. The Pancreatic Langerhans islets were up-regulated in both hyperbaric oxygen therapy and olanzapine treatments but the combination (HBOOLZ) doubled these islets number.Discussion: This study advocated that hyperbaric oxygen therapy can be an alternative approach to control or reverse many metabolic disorders (MDs) associatedwith olanzapine treatment. In addition, it seems that hyperbaric oxygen therapy positively affect the pancreatic Langerhans cells activity and architecture.